Samotne rodzicielstwo w systemie pomocowym państwa - Jurczyk-Romanowska, Ewa (Karkonoska Państwowa Szkoła Wyższa, 2011)
Reflections on the subject of government welfare system aimed at single parents are presented in the article. Changes of civilisation are a cause of an escalation of the phenomenon of single parenthood in Poland, with the number of divorces rising year by year and an increase in the number of people who decide to live in concubinates or become single parents of children born out of wedlock. The withdrawal of the government from numerous forms of support for that social group is observed simultaneously with the aforementioned changes. A choice of labour law, social security and family law regulations is analysed at length in the article dedicated to single parenthood in the government welfare system.
Keywords: samotni rodzice; samotna matka; samotny ojciec; państwo; polityka społeczna